Effectiveness of FDI, technological gap and sectoral level productivity in the Visegrad Group - Kamil Makieła (Technological and Economic Development of Economy, 2021)
The objective of this paper is to investigate the impact of foreign direct investment (FDI) on economic growth and productivity in sectors of the Visegrad Group one decade after their accession to the EU. In order to account for sample heterogeneity, as well as productivity differences, we construct a generalized true random-effects model with varying efficiency distribution. We find that FDI has a positive impact on the Visegrad Group’s sectors and that its effectiveness depends upon the technological gap between the host and home economy. There are three sources of this positive impact: (i) sectoral output and labour productivity growth, (ii) more effective use of input factors, and via (iii) higher efficiency component of the total factor productivity (TFP). These sources form a three-way transmission mechanism through which FDI can impact economic growth conditioned upon FDI effectiveness due to the technological gap.